ANALYSIS OF STUDENTS ERROR ACCORDING TO NEWMAN IN SOLVING MATHEMATICS PROBLEMS OF ALGEBRA IN THE FORM OF STORY IN SECOND GRADE OF SMPN 1 BANDA ACEH - Johan Yunus; Bintang Zaura; Y Yuhasriati (Jurnal Geuthèë: Penelitian Multidisiplin, 2019)
One of the material in mathematics lesson is algebra operation. Algebraic materials require the students to master the concept of algebra that becomes the basis for learning the next material. However, students still make mistakes in solving problems related to algebra operations. Includes the problem solving form of the story problem that adds difficulties for students. The purpose of this study is to find out what the mistakes and causes of mistakes made by students of class VIII SMP Negeri 1 Banda Aceh in solving the story based on Newman procedures. The approach used is a qualitative approach with the type of research is descriptive. Data collection using tests and interviews. The research involves students VIII-1, amounting to 27 students. Subjects of interview research taken 3 of 27 students class VIII-1, with the criteria of students who do a lot errors. Each subject was interviewed related to the results of his work on the algebra operation about story problem. The validity test of the data was done by triangulation technique. The results of the research indicate that the type of mistakes made by the students of grade VIII-1 SMP Negeri 01 Banda Aceh in solving the algebraic story problem are misunderstanding, transforming mistakes, processing skill mistakes, and the error of writing the final answer. Misunderstanding caused by the students forgetting and rushing in doing the problem. The problem of transformation is caused by the weakness of the student’s ability to change the story into algebra and wrong in using the approach. The error of process skill is caused wrongly in calculating algebraic operations. While the error of writing the final answer caused the students did not make conclusions and did not write the final outcome of the settlement. The implication of this study is the need for further research to reduce the students in making the same mistakes. Further research is also needed on the work that students can do to overcome the mistakes made by students as can be seen in this study.